Gene length as a biological timer to establish temporal transcriptional regulation. Issue 3 (1st February 2017) - Kirkconnell, Killeen S.; Magnuson, Brian; Paulsen, Michelle T.; Lu, Brian; Bedi, Karan; Ljungman, Mats
ABSTRACT: Transcriptional timing is inherently influenced by gene length, thus providing a mechanism for temporal regulation of gene expression. While gene size has been shown to be important for the expression timing of specific genes during early development, whether it plays a role in the timing of other global gene expression programs has not been extensively explored. Here, we investigate the role of gene length during the early transcriptional response of human fibroblasts to serum stimulation. Using the nascent sequencing techniques Bru-seq and BruUV-seq, we identified immediate genome-wide transcriptional changes following serum stimulation that were linked to rapid activation of enhancer elements. We identified 873 significantly induced and 209 significantly repressed genes. Variations in gene size allowed for a large group of genes to be simultaneously activated but produce full-length RNAs at different times. The median length of the group of serum-induced genes was significantly larger than the median length of all expressed genes, housekeeping genes, and serum-repressed genes. These gene length relationships were also observed in corresponding mouse orthologs, suggesting that relative gene size is evolutionarily conserved. The sizes of transcription factor and microRNA genes immediately induced after serum stimulation varied dramatically, setting up a cascade mechanism for temporal expression arising from a single activation event. The retention and expansion of large intronic sequences during evolution have likely played important roles in fine-tuning the temporal expression of target genes in various cellular response programs.